Providing adequate housing in SA in the twentieth and twenty first century - Tagg, Jason (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Construction Economics, 2014)
Thesis (BSc. (Hons)(Construction Economics))--University of Pretoria, 2011.